Gait analysis and knee kinematics before surgery, 6 and 18 months after high tibial osteotomy - A. P. Prizov; N. V. Zagorodniy; A. M. Vostrikov; D. V. Skvortsov; G. A. Ayrapetov; F. L. Lazko; A. A. Akhpashev; A. V. Altukhova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Introduction. Corrective knee joint osteotomy is used as a joint-preserving surgery for varus deformity. Longer-term functional outcomes have not been studied well enough yet. The study objective was to assess longer-term functional, clinical, outcomes and gait biomechanics in patients after 6 and 18 months after surgery correction. Object and methods. The study included 20 patients with medial osteoarthritis of the knee of grade 2–3 and a varus deformity of > 4°. A total of 21 surgeries were performed on the patients. Full length weightbearing (FLWB) X-ray and corrective knee joint assessments were done using the KSS, KOOS and VAS scoring systems were obtained from all the patients. Biomechanical gait parameters were captured using an inertial sensor system at the timepoint of before the surgery, 6 months, and 18 months after surgery. Temporal and kinematic parameters of walking were analyzed. Results. The radiological parameters showed stable varus deformity correction. According to the KOOS, KS and VAS scores, there was a moderate dynamic improvement in the operated knee function during the follow-up period before surgery to 6 and to 18 months after surgery. Biomechanical parameters showed an improvement in corrective knee joint function of the operated side in the first 6 months after surgery. In the following year, there were some subjective improvements but without any significant changes in gait biomechanics or knee kinematics. Conclusion. Thus, the main changes in the clinical and functional state occur in the first 6 months after surgery. According to the study data, there was a moderate clinical improvement, as assessed by VAS, KOOS and KSS, in the long-term follow-up period. The biomechanical changes were minor.